Risk factors of HBV intrauterine transmission among HBsAg‐positive pregnant women. Issue 5 (5th December 2012) - Guo, Z.; Shi, X. H.; Feng, Y. L.; Wang, B.; Feng, L .P.; Wang, S. P.; Zhang, Y. W.
Summary Little is known about the risk factors associated with hepatitis B virus (HBV) intrauterine transmission among HBsAg‐positive mothers. We conducted a study in Taiyuan, China, including 1133 HBsAg‐positive mothers and their babies. A total of 101 neonates had HBsAg and/or HBV DNA positive with an intrauterine transmission rate of 8.9%. Maternal menstrual irregularity (OR = 4.95, 95% CI: 1.71, 14.33) and severe nausea during the first trimester (OR = 1.86, 95% CI: 1.11, 3.09) were associated with an increased risk of intrauterine transmission, while caesarean delivery (OR = 0.32, 95% CI: 0.20, 0.51) was associated with a decreased risk after adjusting for potential confounders. Maternal HBeAg positive was a strong independent predictor for intrauterine transmission (OR = 2.56, 95% CI: 1.54, 4.27). A positive association between maternal HBV DNA levels and intrauterine transmission was suggested. Maternal HBIG administration during pregnancy, family history of HBV infection and premature rupture of membranes was not associated with the risk of intrauterine transmission. The study confirmed that maternal HBeAg positive was a risk factor and caesarean delivery was a protective factor for intrauterine transmission. The new findings associated with menstrual irregularity and severe nausea during the first trimester warrant further investigation.